PENGARUH UPAH MINIMUM REGIONAL DAN KESEMPATAN KERJA TERHADAP KRIMINALITAS DI KALIMANTAN TENGAH - Rima Harati (Prosiding Seminar Nasional Indonesia, 2025)
This study aims to analyze the effect of regional minimum wages and job opportunities on crime in Central Kalimantan. This study was conducted in Central Kalimantan between 2014-2024 and the analytical tools used were multiple regression analysis and classical assumptions, which were processed using SPSS 25. The results of the multiple regression analysis explain that regional minimum wages (X1) and job opportunities (X2) do not have a significant effect on crime in Central Kalimantan. The results of the classical assumptions explain that this regression model meets the assumption of normality, there is multicollinearity in this regression model, there are no symptoms of heteroscedasticity in the regression model used, it is concluded that in the regression model there are no symptoms or problems of autocorrelation.